2021
DOI: 10.1080/13607863.2021.1940096
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effect of loneliness and social isolation on health outcomes among older adults

Abstract: Objectives: Loneliness and social isolation are described similarly yet are distinct constructs. Numerous studies have examined each construct separately; however, less effort has been dedicated to exploring the impacts in combination. This study sought to describe the cumulative effects on late-life health outcomes. Method: Survey data collected in 2018-2019 of a randomly sampled population of US older adults, age 65+, were utilized (N = 6,994). Survey measures included loneliness and social isolation using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 56 publications
4
32
2
3
Order By: Relevance
“…Tan et al [37] Case-control study (pilot randomized controlled evaluation) 113 Older adults who were engaging in volunteering showed an increase in their physical activity level Sofi et al [30] Systematic meta-analysis of prospective studies 33,816 Physical activity of all levels showed a protective effect on the occurrence of cognitive decline ATTICA study; Kollia et al [27] Observational population study 853 Higher Healthy Aging Index (which included physical activity) was associated with lower 10-year CVD risk Lindsay-Smith et al [35] Observational population study 28 Group-based social and physical activities programs for older people may improve their well-being and prevent loneliness Xu et al [29] Observational population study 613 Physical activity was associated with a reduced risk of developing metabolic syndrome in the participants with the highest levels of physical activity de Oliveira et al [32] Observational population study 200 There was a correlation between low levels of physical activity and symptoms of anxiety and depression in older people Steltenpohl et al [34] Observational population study 39 Older adults were more likely to prefer to exercise with others, rather than alone Liu et al [31] Meta-analysis of randomized controlled trials 1039 In the elderly with cognitive decline, exercise and nutrition interventions showed a positive effect on global cognitive function Barnes et al [33] Observational population study 6994 Loneliness and social isolation in older people was associated with lower quality of life and higher medical costs picking up physical activity later in life has similar, but smaller benefits for health. Almeida et al conducted a study with 10-13 year follow-up, involving 12,201 older men living in Perth, Australia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tan et al [37] Case-control study (pilot randomized controlled evaluation) 113 Older adults who were engaging in volunteering showed an increase in their physical activity level Sofi et al [30] Systematic meta-analysis of prospective studies 33,816 Physical activity of all levels showed a protective effect on the occurrence of cognitive decline ATTICA study; Kollia et al [27] Observational population study 853 Higher Healthy Aging Index (which included physical activity) was associated with lower 10-year CVD risk Lindsay-Smith et al [35] Observational population study 28 Group-based social and physical activities programs for older people may improve their well-being and prevent loneliness Xu et al [29] Observational population study 613 Physical activity was associated with a reduced risk of developing metabolic syndrome in the participants with the highest levels of physical activity de Oliveira et al [32] Observational population study 200 There was a correlation between low levels of physical activity and symptoms of anxiety and depression in older people Steltenpohl et al [34] Observational population study 39 Older adults were more likely to prefer to exercise with others, rather than alone Liu et al [31] Meta-analysis of randomized controlled trials 1039 In the elderly with cognitive decline, exercise and nutrition interventions showed a positive effect on global cognitive function Barnes et al [33] Observational population study 6994 Loneliness and social isolation in older people was associated with lower quality of life and higher medical costs picking up physical activity later in life has similar, but smaller benefits for health. Almeida et al conducted a study with 10-13 year follow-up, involving 12,201 older men living in Perth, Australia.…”
Section: Resultsmentioning
confidence: 99%
“…Loneliness and social isolation in older age have a negative effect on the quality of life. Increased likelihood of depression and greater medical costs are also connected to these constructs [33]. Therefore, social engagement is often included in definitions of successful and healthy aging.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…The U.S. Centers for Disease Control and Prevention reported that adults 65 years and older are more likely than those of other age groups to die or develop a severe illness leading to hospitalization if they contract the coronavirus [ 9 ], which resulted in recommendations for older adults to stay at home and avoid close contact with others. Already, several studies have reported on the compounding health conditions among older adults—anxiety, depression, loneliness, increasing comorbidities, and the worsening of existing chronic diseases—brought about as they were considered the most vulnerable to COVID-19 [ 10 , 11 , 12 , 13 , 14 ]. These studies also implied that older adults desired a sense of control and preparedness to make medical decisions involving their care [ 10 , 11 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Already, several studies have reported on the compounding health conditions among older adults—anxiety, depression, loneliness, increasing comorbidities, and the worsening of existing chronic diseases—brought about as they were considered the most vulnerable to COVID-19 [ 10 , 11 , 12 , 13 , 14 ]. These studies also implied that older adults desired a sense of control and preparedness to make medical decisions involving their care [ 10 , 11 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation